A DUALIDADE HOMEM E NATUREZA: uma análise contextualmente situada em ambiência de riscos e incertezas - Cláudia Maria da Costa Gonçalves; Jean Carlos Nunes Pereira; Thiago Allisson Cardoso de Jesus (Revista de Políticas Públicas, 2016)
Assuming the conditioned contemporary to assumptions and paradoxes of capitalism, is placed in suspense anthropocentric paradigm, investigating the relationship between man and nature. In this sense, it analyzes the oblivion of biocentrism and multidimensionality of the right to welfare and the future. Discuss the relationship between development and environmental protection in societies marked by insatiable consumption. Peering up the various manifestations of inequality in capitalist societies. Based on the categories of reflexive sociology, was made using the techniques of literature, documentary and discourse analysis. Finally, some representative considerations of scientific research under discussion. Key words: Biocentrism, sustainability, multidimensionality. Recebido em: 09.04.2016. Aprovado em: 06.06.2016. 1 INTRODUÇÃO